Exchange terms in the quark-meson coupling model - Krein, G. (Springer, 2000)
In this talk we report on recent progress in implementing exchange terms in the quark-meson coupling model. Exchange effects are related to the Pauli exclusion principle. We discuss exchange effects at the nucleon level and at the quark level. We also address the incorporation of chiral symmetry and Delta degrees of freedom in the model.